Gone fishin' - Aoyama, Hiroko, author (Colorado State University. Libraries, 1998)
The characteristics of the art I create are strongly influenced by two strikingly different cultures of East and West. I was born, raised, and educated in Japan, but more than thirty years of my life have been spent in the United States. Hence, my work may reveal certain qualities that appear simultaneously both familiar and exotic to the viewers. My motive for developing such art is to purposely create visual tensions between the familiar and the exotic within the context of the multiculturalism. In addition, my works are intended to manifest a multitude of subtle ambiguities about their meanings so as to enable viewers to exercise their imagination and create their own dialogue with the sculpture.
Zip file contains 15 slides of artist's works.
Keywords: Aoyama, Hiroko